Right to privacy and legal recognition of gender identity in Serbia: Constitutional Court of Serbia at work - Papić Tatjana (Anali Pravnog Fakulteta u Beogradu)
This paper discusses different issues pertaining to a 2012 landmark decision of the Constitutional Court of Serbia on the legal recognition of surgical gender reassignment. In this case, the SCC made a substantial contribution to the protection of human rights, in general, and an important contribution for the protection of the rights of transgender persons, in particular. The former was achieved by the interpretation that art. 23 of the Constitution on the right to dignity and free development of individuals included protection of the right to privacy and family life (which was omitted in the list of rights guaranteed by the Constitution), interpreting the scope of this right in accordance with ECtHR standards. The latter was done by analogous application of the existing Act on Public Registries to situations in which medical gender reassignment was conducted to enable the necessary changes be made in the birth register. By the virtue of this, the SCC took an active approach in filling a lacuna in the Serbian legal system. This paper also strives to examine impact of the SCC decision on the protection of rights of transgender persons and the current normative setting in respect to this vulnerable group in Serbia. It shows that the decision of the SCC remains the only legal basis on which transgender persons who have undergone a gender reassignment operation in Serbia can rely upon. However, bearing in mind Serbia's EU aspiration and the fact that the EU Commission has been continuously noting that Serbia lacks in regulation in this field, one should expect improvements, since EU integration seems to be the most effective tool for legislative and policy changes in Serbia.